Agro-residual biomass and disposable protective face mask: a merger for converting waste to plastic-fiber fuel via an integrative carbonization-pelletization framework - Moreira, Bruno Rafael de Almeida; Cruz, Victor Hugo; Barbosa Júnior, Marcelo Rodrigues; Meneses, Mariana Dias; Lopes, Paulo Renato Matos; da Silva, Rouverson Pereira (Biomass conversion and biorefinery, 2024)
Incineration and landfilling offer possibilities for addressing high-rate management of COVID-waste streams. However, they can be costly and environmentally unsustainable. In addition, they do not allow to convert them to fuels and chemicals as waste-to-energy and waste-to-product technologies. Therefore, we analyzed whether integrating hydrothermal carbonization (HTC) and pelletization can allow converting the surgical face mask (SFM) and biomass to composite plastic-fiber fuel (CPFF). We blended the plastic material and corncob, peanut shell, or sugarcane bagasse at the proportion of 50:50 (%, dry mass basis) for HTC. We performed the thermal pretreatment of blends in an autoclaving reactor at 180 °C and 1.5 MPa. Then we pelletized the hydrochars in a presser machine at 200 MPa and 125 °C. By analyzing the evidence from our study, we recognized the viability of combining the SFM and agricultural residues for CPFF from comparable technical features of our products to standards for premium-grade wood pellets. For instance, the elemental composition of their low-meltable ash was not stoichiometrically sufficient to severely produce slagging and fouling in the equipment for thermal conversion. Although they contained synthetic polymers in their structures, such as polyethylene from filter layers and nylon from the earloop, they emitted CO and NO x below the critical limits of 200 and 500 mg m −3 , respectively, for occupational safety. Therefore, we extended the knowledge on waste-to-energy pathways to transform SFM into high-quality hybrid fuel by carbonization and pelletization. Our framework can provide stakeholders opportunities to address plastic and biogenic waste in the context of a circular economy.